Die dilemma van die musiekwetenskaplike in die onderrigsituasie - Spies, Bertha (Koers, 1995)
The dilemma of the musicologist who is also a teacher. In this article a main educational objective, namely the interpretation of reality, forms the basis for discussing the dilemma of the musicologist who is also a teacher. Firstly, various facets of musical reality are discussed under the following headings: the meaning of reality for the musicologist, artistic representation of reality and an idealized musical reality. Secondly, the manner in which musical reality is interpreted is discussed. Thirdly, results of a fragmented musical reality are mentioned and finally, proposals aimed at solving the problem of the musicologist-teacher are put forward, arguing for a more objective view of reality as a whole, stressing the double responsibility of the musicologist-teacher to interpreting difficult texts and the necessity to re-evaluate traditional theories in the light of their didactic effectiveness.